Climate Policy in Global and Local Aspects - Wiszniowski, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A review article summarising the current state of knowledge and suggesting directions for further research. It is part of a wider review aimed at assessing the effectiveness of climate change policies. The main difficulties considered in the article include the problems of environmental management and strategies for building resilience to climate change induced stress. The issues analysed in the article concern selected problems in the implementation of climate policy at global, regional and local levels. It was found that, under certain conditions, the effects of the measures taken can be counterproductive. The effectiveness and rationality of climate policy was also analysed from an economic perspective.
Keywords: climate policy; adaptation plans; carbon dioxide emissions reduction; energy crisis; security and economic balance of climate policy